Peningkatan Keterampilan Sosial Siswa Melalui Metode Bermain Peran Siswa Kelas V Sekolah Dasar Ringkas dan Informatif - Rohmatul Ummah (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2019)
This study aims to improve the social skills of V.C class students through role playing methods. This research is a classroom action research with research subjects of V.C class of SD Muhammadiyah Karangkajen, Yogyakarta. This study focuses on improving students' social skills. Data collection techniques are obtained through observation, interviews and measurements through social skills scale. The analysis technique used is by comparing the results of social skills before and after the action. The results of this study are an increase in the scores of students' social skills. From pre-cycle activities to cyclum II experienced an increase in the number of students in the high category. Prasiklus shows 68% of students fall into the high category, then increase to 92% in cycle I and cycle II. Based on the results of cycles I and II show that the role playing method as one of the learning methods to improve students' social skills.